FAKTOR-FAKTOR PENYEBAB KEJADIAN STUNTING PADA BALITA DI DESA SIMARIGUNG KECAMATAN DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN - Manullang, Putri A.E.; Seriga Banjarnahor (JOURNAL SAINS STUDENT RESEARCH, 2025)
Stunting, or short stature, is a chronic malnutrition problem caused by prolonged nutritional deficiency, resulting in growth disorders in children. The purpose of this study was to determine the factors causing stunting based on parity, family income, duration of breastfeeding, availability of clean water, and mothers' knowledge about stunting. This study used a descriptive analytical method with a cross-sectional design. The population consisted of 123 individuals, and the sample size was determined using the Slovin formula, resulting in 50 participants. Data were collected using questionnaires and analyzed using the chi-square test. This study shows that parity has a significant effect on stunting using a chi-square test with a 90% confidence level and df= 3, yielding a calculated ????2 (9.058) >????2table (6.251) and a p-value of 0.02<0.05. The family income variable has a significant relationship with the incidence of stunting using a chi-square test with a confidence level of 90% and df = 3, yielding a calculated ????2 (10.495) >????2 table (6.251) and a p-value of 0.01<0.05. The variable of duration of exclusive breastfeeding has a significant relationship with the incidence of stunting using a chi-square test with a confidence level of 90% and df = 1, yielding a calculated χ² (6.549) > table χ² (2.705) and a p-value of 0.01<0.05. The variable of mothers' knowledge about stunting has a significant relationship with the incidence of stunting using the chi-square test with a confidence level of 90% and df = 2 obtained. Calculated ????2 (7.274) > table ????2 (4.605 and p-value 0.02<0.05.